A Comparative Study of Educational Policy Promoting Digital Citizenship in Thailand, Singapore, and Malaysia - Boonanek, Suwanan; Bangchuad, Doungkamol (An Online Journal of Education, 2022)
This comparative study aimed to investigate educational policies promoting digital citizenship at the basic education level (K-12) in Thailand, Singapore, and Malaysia. The study used qualitative research methods, documentary research, and semi-structured interviews, and the population used for the study consisted of eight policymakers and practitioners. The results found that one commonality between these three countries was the belief that digital technology plays an integral part in becoming a digital society; however, the educational policy at the basic education level in Thailand remains unclear. Furthermore, the factors contributing to the success of an educational policy promoting digital citizenship include 1) precise policy formulation and continuity in policy implementation, and 2) support from stakeholders, policymakers, practitioners, and researchers.